Fremtidens sygepleje i den kommunale sygepleje: – faglighed eller styret funktion? - Laugesen, Janne Bryde (Tidsskrift for Professionsstudier, 2024)
This article examines discussions about home nursing professionalism in the emergence of the municipal healthcare system. Based on a registrant analysis based on Ejersbo and Greve's projection of the modernization of the public sector and a professional theoretical understanding of professionalism, the article examines how home nursing professionalism is articulated in internal and external texts on home nursing professionalism in the municipal sector in the period 1983-2005. It then examines how home nursing professionalism is shaped through internal and external struggles over time. This is seen in relation to Julia Evett's concepts of professional theory and contemporary expectations of home nursing.